Differential alterations of cortical glutamatergic binding sites in senile dementia of the Alzheimer type. - Chalmers, D T (1990)
Involvement of cortical glutamatergic mechanisms in senile dementia of the Alzheimer type (SDAT) has been investigated with quantitative ligand-binding autoradiography. The distribution and density of Na(+)-dependent glutamate uptake sites and glutamate receptor subtypes--kainate, quisqualate, and N-methyl-D-aspartate--were measured in adjacent sections of frontal cortex obtained postmortem from six patients with SDAT and six age-matched controls. The number of senile plaques was determined in the same brain region. Binding of D-[3H]aspartate to Na(+)-dependent uptake sites was reduced by approximately 40% throughout SDAT frontal cortex relative to controls, indicating a general loss of glutamatergic presynaptic terminals. [3H]Kainate receptor binding was significantly increased by approximately 70% in deep layers of SDAT frontal cortex compared with controls, whereas this binding was unaltered in superficial laminae. There was a positive correlation (r = 0.914) between kainate binding and senile plaque number in deep cortical layers. Quisqualate receptors, as assessed by 2-amino-3-hydroxy-5-[3H]methylisoxazole-4-propionic acid binding, were unaltered in SDAT frontal cortex compared with controls. There was a small reduction (25%) in N-methyl-D-aspartate-sensitive [3H]glutamate binding only in superficial cortical layers of SDAT brains relative to control subjects. [3H]Glutamate binding in SDAT subjects was unrelated to senile plaque number in superficial cortical layers (r = 0.104). These results indicate that in the presence of cortical glutamatergic terminal loss in SDAT plastic alterations occur in some glutamate receptor subtypes but not in others.